In Tune with the Infinite; or, Fullness of Peace, Power, and Plenty - Trine, Ralph Waldo, 1866-1958 (Salt Lake City, UT : Project Gutenberg, 2007)
"In Tune with the Infinite; or, Fullness of Peace, Power, and Plenty" by Ralph Waldo Trine is a philosophical treatise written in the late 19th century. The work explores themes of spirituality, the power of thought, and the connection between the individual and the Infinite Source of Life. It aims to guide readers toward realizing their inherent potential for peace, power, and abundance through an understanding of spiritual laws. The beginning of the book sets the stage for its exploration of how one's internal thoughts and beliefs shape external realities. Trine emphasizes that individuals are the architects of their own lives, building their realities through their internal states of being. The author discusses the duality of the optimist and pessimist, suggesting that perspectives significantly influence life outcomes. He introduces the concept of the Infinite Spirit as the source of life and encourages readers to cultivate a conscious realization of their connection to this source to experience fulfillment and transformation in their lives. (This is an automatically generated summary.)
Release date is 2007-11-20
E-text prepared by Al Haines
Keywords: New Thought